Cloud Computing and Security: First International Conference, ICCCS 2015, Nanjing, China, August 13-15, 2015. Revised Selected Papers - Huang, Zhiqiu; Sun, Xingming; Luo, Junzhou; Wang, Jian (LNCS sublibrary. SL 3, Information systems and applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the proceedings of the International Conference on Cloud Computing and Security (ICCCS 2015) will be held on August 13-15, 2015 in Nanjing, China. The objective of ICCCS 2015 is to provide a forum for researchers, academicians, engineers, industrial professionals, students and government officials involved in the general areas of information security and cloud computing.